DRAMATURGI KOMUNIKASI POLITIK IDRIS S.IPEM PADA PEMILIHAN LEGISLATIF 2024 - Mulyana (LPPM Universitas Muhammadiyah Bulukumba, 2025)
Abstract: This study analyzes the political communication strategy of Idris S.Ipem during the 2024 Legislative Election using Erving Goffman’s dramaturgy approach. The primary focus is on how Idris constructed his political image through front stage (public performance) and back stage (behind-the-scenes preparation) while managing impressions to gain public support. Employing a descriptive qualitative method, data were collected through in-depth interviews with key informants, observations, and document analysis. The findings reveal that Idris effectively built an image as a people-centric leader by promoting programs such as PIP scholarships, home renovations, and free ambulance services, while controlling information dissemination through a dedicated media team. The discussion integrates these findings with dramaturgy theory, highlighting contributions to political communication in Indonesia. In conclusion, Idris’s dramaturgical strategy successfully enhanced his electability as a new candidate, with implications for authentic and inclusive political campaign practices. Keywords: Political Communication, Dramaturgy, Impression Management, Legislative Election, Idris S.Ipem Abstrak: Legislatif 2024 menggunakan pendekatan dramaturgi Erving Goffman. Fokus utama adalah bagaimana Idris membangun citra politik melalui panggung depan (front stage) dan panggung belakang (back stage), serta mengelola impresi untuk menarik dukungan masyarakat. Dengan metode kualitatif deskriptif, data dikumpulkan melalui wawancara mendalam dengan informan kunci, observasi, dan analisis dokumen. Hasil menunjukkan bahwa Idris efektif membangun citra sebagai pemimpin merakyat melalui sosialisasi program seperti beasiswa PIP, bedah rumah, dan layanan ambulans gratis, sambil mengontrol informasi melalui tim media. Pembahasan mengintegrasikan temuan dengan teori dramaturgi, menyoroti kontribusi pada komunikasi politik di Indonesia. Simpulan: Strategi dramaturgi Idris berhasil meningkatkan elektabilitasnya sebagai calon baru, dengan implikasi untuk praktik kampanye politik yang autentik dan inklusif. Kata kunci: Komunikasi Politik, Dramaturgi, Manajemen Impresi, Pemilihan Legislatif, Idris S.Ipem